VALUE BASED AND MARKET BASED AS PREDICTORS OF STOCK PRICES IN LQ45 COMPANY - Arna Suryani (Jurnal Reviu Akuntansi dan Keuangan, 2017)
This study aims to obtain empirical evidence whether value added and market value is predictorof stock prices. The value based concepts is measured by economic value added and marketbased concepts measured by market value added. The object of study is index LQ45 companieslisted in Indonesian Stock Exchange period 2012-2016. The selection of samples based on purposive sampling with certain criteria and selected as many as 18 companies index LQ45. The dataused in this research is secondary data using quantitative approach. Further testing will bedone by classical assumptions against the data collected using regression analysis and testhypothesis F and t.The results of this study prove empirically that together Economic Value Added and MarketValue Added is positive and significant predictor of the company’s stock price because the significant is 0.000 smaller than 0.05. Partially significant level of 0.05 EVA has a negative effectof 0.14 on stock prices, it can be concluded that the EVA is a predictor variable has a negativeeffect that is not significant to stock prices at index LQ45. Significant level of MVA that is equalto 0.000 smaller than the significant level of 0.05. MVA positive influence of 0.599 to stock price.It can be concluded that the partial variable MVA positive effect is a significant predictorvariable to stock prices at index LQ45.Keyword:economic value added, market value added, financial performance, stock price